DISSEMINATION OF ROSE PRESERVATION TECHNOLOGY AND FINANCIAL RECORDING TO INCREASE COMMUNITY'S INCOME - Oktaroza, Magnaz Lestira; Santoso, Gatot; Suganda, Fitrin Rawati (Kajian Akuntansi, 2024)
The snack business conducted by the residents of Cintamanik Village has struggled to compete with snacks marketed in Garut, resulting in an insignificant increase in their income. In light of these circumstances, the PKM Team conducted training activities to introduce flower preservation technology to produce preserved roses with high market value. Additionally, training sessions focus on financial management, packaging design, and digital marketing via online marketplaces were provided as marketing tools. The research employed a descriptive analysis by processing primary data through pre-test and post-test of 32 entrepreneurs as respondents. The test outcome indicate an improvement from the pre-test results to the post-test results, indicating that the conducted training significantly enhanced the participants' abilities and knowledge. Particularly, the training enhances skills in preserved rose production and product marketing, facilitating income growth for the participants. Keywords     : Preserved Roses Technology, Cost of Production, Marketplace.